Implementing a Data to Care Strategy to Improve Health Outcomes for People With HIV: A Report From the Care and Prevention in the United States Demonstration Project. (November 2018) - Sweeney, Patricia; Hoyte, Tamika; Mulatu, Mesfin S.; Bickham, Jacquelyn; Brantley, Antoine D.; Hicks, Curt; McGoy, Shanell L.; Morrison, Melissa; Rhodes, Anne; Yerkes, Lauren; Burgess, Samuel; Fridge, Jessica; et al.
Objectives: The Care and Prevention in the United States Demonstration Project included implementation of a Data to Care strategy using surveillance and other data to (1) identify people with HIV infection in need of HIV medical care or other services and (2) facilitate linkages to those services to improve health outcomes. We present the experiences of 4 state health departments: Illinois, Louisiana, Tennessee, and Virginia. Methods: The 4 state health departments used multiple databases to generate listings of people with diagnosed HIV infection (PWH) who were presumed not to be in HIV medical care or who had difficulty maintaining viral suppression from October 1, 2013, through September 29, 2016. Each health department prioritized the listings (eg, by length of time not in care, by viral load), reviewed them for accuracy, and then disseminated the listings to staff members to link PWH to HIV care and services. Results: Of 16 391 PWH presumed not to be in HIV medical care, 9852 (60.1%) were selected for follow-up; of those, 4164 (42.3%) were contacted, and of those, 1479 (35.5%) were confirmed to be not in care. Of 794 (53.7%) PWH who accepted services, 694 (87.4%) were linked to HIV medical care. The Louisiana Department of Health also identified 1559 PWH as not virally suppressed, 764 (49.0%) of whom were eligible for follow-up. Of the 764 PWH who were eligible for follow-up, 434 (56.8%) were contacted, of whom 269 (62.0%) had treatment adherence issues. Of 153 PWH who received treatment adherence services, 104 (68.0%) showed substantial improvement in viral suppression. Conclusions: The 4 health departments established procedures for using surveillance and other data to improve linkage to HIV medical care and health outcomes for PWH. To be effective, health departments had to enhance coordination among surveillance, care programs, and providers; develop mechanisms to share data; and address limitations in data systems and data quality.